(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
Carbon dots (CDs) are a class of Carbon-based nanomaterials, typically smaller than 10 nm, known for their excellent optical properties, biocompatibility, and environmental friendliness. Their synthesis involves a variety of methods, including top-down approaches like arc-discharge and laser ablation, as well as bottom-up techniques such as hydrothermal and pyrolysis processes. The choice of precursor materials, which can range from organic molecules to waste biomass, and the synthesis method significantly influence the size, surface functionality, and quantum yield of the resulting carbon dots.